Mode locking of an all-fiber laser by acousto-optic superlattice modulation - Cuadrado Laborde, Christian Ariel (2009)
Active mode locking of an erbium-doped all-fiber laser with a Bragg-grating-based acousto-optic modulator is demonstrated. The fiber Bragg grating was acoustically modulated by a standing longitudinal elastic wave, which periodically modulates the sidebands at twice the acoustic frequency. The laser has a Fabry– Perot configuration in which cavity loss modulation is achieved by tuning the output fiber Bragg grating to one of the acoustically induced sidebands. Optical pulses at 9 MHz repetition rate, 120 mW peak power, and 780 ps temporal width were obtained. The output results to be stable and has a timing jitter below 40 ps. The measured linewidth, 2.8 pm, demonstrates that these pulses are transform limited.